Mediating Role of Tourist Trust in the Relationship between Digital Marketing, Destination Image, and Tourists’ Visit Decisions - Agnes Febriyani; Aang Curatman (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the influence of digital marketing and destination image on tourists’ visit decisions, with tourist trust positioned as a mediating variable in tourism destinations.Method: This study adopted a quantitative research design using a survey method. Data were collected through questionnaires distributed to 204 tourists who had visited tourism destinations in Cirebon Regency, Indonesia. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS).Result: The findings reveal that digital marketing and destination image have positive and significant effects on tourists’ visit decisions. Digital marketing and destination image also significantly influence tourist trust. Furthermore, tourist trust partially mediates the relationships between digital marketing, destination image, and tourists’ visit decisions.Practical Implications for Economic Growth and Development: The findings suggest that strengthening digital marketing strategies and improving destination image can enhance tourist trust and encourage visit decisions, thereby contributing to tourism sector growth. These efforts may support regional economic development by increasing tourist arrivals, local revenue, and tourism-related economic activities.Originality/Value: This study integrates digital marketing and destination image into a mediation framework by incorporating tourist trust as an explanatory mechanism for tourists’ visit decisions. In addition, this study enriches the literature on digital tourism marketing, particularly in emerging regional tourism destinations.